2017
DOI: 10.22158/jepf.v3n4p507
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Power Parity Theory and Applications for Solomon Islands

Abstract: We have tested the purchase power parity hypothesis using the consumer price index of USA and UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…According to Paul and Motlaleng (2008), nominal exchange rate changes may not pass through to domestic prices. Paul et al (2017) confirmed that this finding is in line with the work of Paul and Motlaleng (2008) who found that the lack of competition in Bostwana's wholesale sector allows importers to take advantage of the currency appreciation in their profit margins whilst only passing the negative impact of depreciation to consumers. Furthermore, these results highlight areas for future research namely into probing the exchange rate pass through effect in the Solomon Islands and the need to calculate its own REER index to verify the results obtained.…”
Section: Hnkpc Modelsupporting
confidence: 88%
“…According to Paul and Motlaleng (2008), nominal exchange rate changes may not pass through to domestic prices. Paul et al (2017) confirmed that this finding is in line with the work of Paul and Motlaleng (2008) who found that the lack of competition in Bostwana's wholesale sector allows importers to take advantage of the currency appreciation in their profit margins whilst only passing the negative impact of depreciation to consumers. Furthermore, these results highlight areas for future research namely into probing the exchange rate pass through effect in the Solomon Islands and the need to calculate its own REER index to verify the results obtained.…”
Section: Hnkpc Modelsupporting
confidence: 88%